The concept of grade in mineral deposits - Esterhuizen, Anton G (Rhodes University, Faculty of Science, Department of Geology, 1983)
The grade of a mineral deposit is determined by the effectiveness of a geological ore forming process, which is the result of the interaction between an ore forming mechanism and the environment in which it operates. Properties of a mineral deposit controlled by ore forming processes include the distribution, density and nature of ore minerals and gangue, and the metal content and impurities of the ore minerals. More efficient ore forming processes tend to develop in the larger mineralizing systems giving rise to richer deposits. As the geological environment within which a mineral deposit evolves becomes more complex a greater number of variables interact to determine the grade of the deposit. This is reflected in the greater variability of the grade distribution, resulting in greater difficulties in obtaining reliable estimates of the recoverable grade, and increased difficulties in the processing of ores. In response to economic fluctuations the working grade of heterogeneous orebodies, that form in geologically complex environments, can often be altered to ensure the continued viability of a mining venture. In contrast the evenly mineralized orebodies that tend to develop in geologically simple environments do not have this flexibility. All the important decisions in the mining industry, such as feasibility studies, choice of ~ining and processing methods, selection and planning, are made on the basis of, or are related to, grade estimates. If the geological controls of grade are fully understood, then it is possible to optimize the selection of the various mining alternatives, leading to the efficient exploitation of ore deposits.
Keywords: Mines and mineral resources; Ore deposits; Mineralogy; Geology, Economic